A novel approach based on enzymatic hydrolysis for the valorisation of edible Parmigiano Reggiano cheese rinds. (November 2022) - Tedeschi, Tullia; Prandi, Barbara; Lolli, Veronica; Gasparini, Alessandra; Leni, Giulia; Loffi, Cecilia; Nocetti, Marco; Pizzamiglio, Valentina; Caligiani, Augusta
Abstract: The growing market for shredded cheeses (such as flakes, internal cylinders, snacks and portions without rind) generates a large amount of Parmigiano Reggiano (PRRE) rind by-products. With the aim to provide a valorisation route for edible PRRE rinds, enzymatic hydrolysis methods were performed to produce a protein hydrolysate starting from the rinds at two ripening stages (12 and 24 months), which were previously characterised for their proximate composition. The results showed that, compared with the inner, the rind section has significantly higher protein (42.4% versus 29.7%) and lipid percentages (36.6% versus 29.7%), due to the lower moisture content (15.7% versus 32.4%). Then, after a single step of enzymatic hydrolysis, high-quality high-protein ingredients with low lipid amount (10–20%) and high digestibility (especially for the high amount of free amino acids at about 50 g 100 g −1 cheese) were obtained, to be potentially used in different food applications.